2019
DOI: 10.1029/2019gl082236
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Impact Study of CYGNSS Ocean Surface Wind Speeds on Numerical Simulations of Hurricanes

Abstract: The NASA Cyclone Global Navigation Satellite System (CYGNSS) was launched in December 2016, providing an unprecedented opportunity to obtain ocean surface wind speeds including wind estimates over the hurricane inner‐core region. This study demonstrates the influence of assimilating an early version of CYGNSS observations of ocean surface wind speeds on numerical simulations of two notable landfalling hurricanes, Harvey and Irma (2017). A research version of the National Centers for Environmental Prediction op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…In the past few decades, TC prediction has observed moderate improvements (Alley et al, ; DeMaria et al, ; Rappaport et al, ). These improvements have mainly resulted from better assimilation of high‐resolution remote sensing observations (e.g., Cui et al, ; Honda et al, ; McNally et al, ; Zhang et al, ; Zhang et al, ; Zhang & Weng, ), increased model resolution (e.g., Bender et al, ; Davis et al, ; Gopalakrishnan et al, ; Hazelton et al, ), and improved model physics (e.g., Gallus & Bresch, ; Gopalakrishnan et al, ; Bao et al, ; Chen, Zhang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, TC prediction has observed moderate improvements (Alley et al, ; DeMaria et al, ; Rappaport et al, ). These improvements have mainly resulted from better assimilation of high‐resolution remote sensing observations (e.g., Cui et al, ; Honda et al, ; McNally et al, ; Zhang et al, ; Zhang et al, ; Zhang & Weng, ), increased model resolution (e.g., Bender et al, ; Davis et al, ; Gopalakrishnan et al, ; Hazelton et al, ), and improved model physics (e.g., Gallus & Bresch, ; Gopalakrishnan et al, ; Bao et al, ; Chen, Zhang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that the simulated CYGNSS data would positively impact the forecasts of TCs in both track and intensity [35][36][37][38][39]. The assimilation of real CYGNSS observation was recently investigated by Cui et al [14]; the authors indicated the potential of CYGNSS data in improving the track, intensity, and structure of TCs. Unfortunately, due to data quality issues, Cui et al [14] were only able to assimilate CYGNSS v2.0 fully developed seas (FDS) data, which greatly underestimates the wind field within deep convection regions related to TCs.…”
Section: Introductionmentioning
confidence: 99%
“…Each CYGNSS observatory is capable of sampling 4 different specular reflection tracks at a frequency of 1 Hz, and ocean surface wind speed is retrieved along the specular tracks at a resolution of approximately 25 km. It is expected that the CYGNSS will be able to accurately monitor the rapidly changing wind of precipitating regions over the tropics (e.g., [13]), and to improve forecasting operations (e.g., [14]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them agree on the potentiality of CYGNSS wind speed assimilation in improving both kinematic and thermodynamic features of TC forecasts. While this article is being written, only Cui et al [10] show a study based on real CYGNSS wind speed assimilation in forecast experiments. These experiments relate to hurricanes Harvey and Irma, which made landfall on U.S. coasts during summer 2017.…”
mentioning
confidence: 99%